Implementasi Manajemen Berbasis Sekolah untuk Meningkatkan Mutu Pendidikan di SMA Negeri 1 Sungai Kakap Kabupaten Kubu Raya - Hendra Wahyudin; Usman Radiana; Luhur Wicaksono (Manajemen Pendidikan, 2024)
The implementation of school-based management is expected to increase the independence of schools in allocating available resources. This study used a descriptive method with a qualitative approach. The method for determining subjects was done using the Purposive Sampling technique. Data collection techniques consisted of observation, interviews, and documentation. Data analysis used an interactive model by Milles and Huberman. The technique for checking data validity used source triangulation, technical triangulation, time triangulation, and member checks. The research results obtained are as follows: (1) school-based management planning is carried out by formulating, establishing, and developing the school’s vision, mission, and goals, identifying school needs, and compiling a work program, (2) implementation is conducted by creating an organizational structure, carrying out various school activities according to the school work program, and following the principles of independence, partnership, transparency, and accountability, (3) evaluation is done by monitoring programs, conducting school self-evaluation, and assessing the achievement of work programs, (4) supporting factors include complete and appropriate facilities and infrastructure, quality teachers and educational staff, good partnerships with various parties, a unique school culture, and a strong sense of nationalism, (5) inhibiting factors include the unavailability of water sources in the school environment and the suboptimal empowerment of teachers and educational staff. In conclusion, the implementation of school-based management has improved the quality of education at Senior High School 1 Sungai Kakap, Kubu Raya Regency.